Islam yang mengayomi : sebuah pemikiran K.H. Hasyim Muzadi - Rasyid, Muhammad Makmun, 1992- (Jakarta, Indonesia : PT Elex Media Komputindo, 2018)
Thoughts of Hasyim Muzadi on Islam in Indonesia.
Includes bibliographical references (pages 201-203).
Keywords: Ulama -- Indonesia; Muzadi, A. Hasyim, -- 1944-2017.; Islam -- Indonesia